IDH‐mutant brainstem gliomas in adolescent and young adult patients: Report of three cases and review of the literature. (7th May 2021) - Chang, Ellen K.; Smith‐Cohn, Matthew A.; Tamrazi, Benita; Ji, Jianling; Krieger, Mark; Holdhoff, Matthias; Eberhart, Charles G.; Margol, Ashley S.; Cotter, Jennifer A.
Abstract : Isocitrate dehydrogenase (IDH) mutations are rare in pediatric and adolescent gliomas. We recently identified three adolescent/young adult (AYA) patients with IDH‐mutant low grade gliomas of the brainstem with several key clinicopathologic and molecular features in common. We discuss these three cases and review the current literature.